2004
DOI: 10.1291/hypres.27.859
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Multicomponent Program (Patient-Centered Assessment and Counseling for Exercise plus Nutrition [PACE+ Japan]) for Lifestyle Modification in Patients with Essential Hypertension

Abstract: With conventional lifestyle modification programs, it can be difficult for hypertensive individuals to modify their lifestyles and maintain the changes. We assessed whether a multicomponent program (patient-centered assessment and counseling for exercise plus nutrition [PACE Japan]) based on behavior theory and social cognitive theory would be effective for treating patients with essential hypertension. We examined 57 outpatients aged 62 10 years with essential hypertension irrespective of antihypertensive dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…We have previously reported that there is no obvious reduction in the actual salt intake in saltconscious patients (13). Thus, repeated monitoring of urinary salt excretion, along with providing feedback to patients and follow-up counseling, seem to be the most important and practical way to achieve a reduction of salt intake in individual hypertensives (13,19).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that there is no obvious reduction in the actual salt intake in saltconscious patients (13). Thus, repeated monitoring of urinary salt excretion, along with providing feedback to patients and follow-up counseling, seem to be the most important and practical way to achieve a reduction of salt intake in individual hypertensives (13,19).…”
Section: Discussionmentioning
confidence: 99%
“…The third study by Miura et al (2004) There were no significant differences in diastolic blood pressure among the three groups (no p values given). There was also significant decreases in percentage of body fat, urine sodium and total energy intake and significant increases in total energy expenditure and exercise energy expenditure for the PACE + Japan follow-up group.…”
Section: Dose Dependent Effects Of MImentioning
confidence: 86%
“…Eight studies were identified and reviewed. Following a critical appraisal of the literature findings, five of the eight studies captured in the review highlight significant decreases in blood pressure related to the MI intervention (Ma et al, 2014;Ogedegbe et al, 2008;Schoenthaler et al, 2015;Svetkey et al, 2009;Woollard et al, 1995) and one study illustrated a non-significant decrease in systolic blood pressure (Miura et al, 2004). The remaining two studies showed no effect on blood pressure but did illustrate other efficacious effects on cholesterol, exercise capacity specifically minutes of walking per week and HbA1c levels (Hardcastle et al, 2013;Willard-Grace et al, 2015).…”
Section: Chapter 5: Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations